2019
DOI: 10.3390/en12142678
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Food and Agricultural Residues for a Flexible Biogas Production: Process Stability and Effects on Needed Biogas Storage Capacities

Abstract: Biogas plants can contribute to future energy systems’ stability through flexible power generation. To provide power flexibly, a demand-oriented biogas supply is necessary, which may be ensured by applying flexible feeding strategies. In this study, the impacts of applying three different feeding strategies (1x, 3x and 9x feeding per day) on the biogas and methane production and process stability parameters were determined for a biogas plant with a focus on waste treatment. Two feedstocks that differed in (1) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…The balance between methanogens and acidogens is the key for a successful BioH 2 and BioCH 4 production, together with the sufficient soluble component available in the substrate for the anaerobic digestion. Notably, several molecular techniques such as terminal restriction fragment length polymorphism (T-RFLP) 54 , ribosomal intergenic spacer analysis (RISA) 55 , quantitative real-time PCR (q-PCR) 56 , fluorescent in-situ hybridization (FISH) 57 , denaturing gradient gel electrophoresis (DGGE) 18,32 and next generation sequencing (NGS) 58 have been extensively studied to identify the archaeal community population in biogas production systems. Although, NGS method has been recommended recently for the comprehensive analysis of bacterial community composition in heterogeneous environments.…”
Section: Discussionmentioning
confidence: 99%
“…The balance between methanogens and acidogens is the key for a successful BioH 2 and BioCH 4 production, together with the sufficient soluble component available in the substrate for the anaerobic digestion. Notably, several molecular techniques such as terminal restriction fragment length polymorphism (T-RFLP) 54 , ribosomal intergenic spacer analysis (RISA) 55 , quantitative real-time PCR (q-PCR) 56 , fluorescent in-situ hybridization (FISH) 57 , denaturing gradient gel electrophoresis (DGGE) 18,32 and next generation sequencing (NGS) 58 have been extensively studied to identify the archaeal community population in biogas production systems. Although, NGS method has been recommended recently for the comprehensive analysis of bacterial community composition in heterogeneous environments.…”
Section: Discussionmentioning
confidence: 99%
“…[10] have covered a lot of ground in development and improvement of the used technologies. The first-generation technologies created in the beginning provided industrial manufacturing of the three main types of BF: Bioethanol, biodiesel, and biogas [30][31][32]. At this stage, starch-containing agriculture products were mainly used as raw materials.…”
Section: General Trends Of Biofuel Production Development and Some Prmentioning
confidence: 99%
“…Scheme of the main steps made during the technological evolution in biofuel (BF) production. G1-first generation technologies [30][31][32][48][49][50][51][52]; G2-second generation technologies [34,39,49,52]; G3-third generation technologies [36,[40][41][42][53][54][55]; G4-fourth generation technologies [45,47].…”
Section: General Trends Of Biofuel Production Development and Some Prmentioning
confidence: 99%
“…to flexible biogas production have been tested concerning the frequency of feeding events, the organic loading rate, and different feedstock mixtures [4,[10][11][12]. It was also shown that significantly higher biogas and methane yields can be achieved with intermittent supply versus continuous (hourly) supply [12][13][14]. Nevertheless, ample amounts of feedstock, especially fast degradable carbohydrates, can be a stress factor for anaerobic digestion (AD) causing process failure in the worst case [3,5].…”
Section: Introductionmentioning
confidence: 99%